1958
DOI: 10.1002/pol.1958.1202711522
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of vinyl stearate by high energy electrons

Abstract: Vinyl stearate has been polymerized by 1000 kv. electrons with field intensities ranging from 1.0 × 103 to 20 × 103 rep per second; the polymers are considered to be branched. A discontinuity of reaction rate and molecular weight with respect to temperature was noted in the vicinity of monomer melting point, and it is suggested that in this temperature region, the diffusion constant for propagation is easily affected. A linear relationship between field intensity and polymerization rate, and a constancy in mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1959
1959
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Table V oligomer than a high molecular weight polymer. These results are consistent with characterization studies conducted by other researchers (32,45).…”
Section: Viscosity Average Molecular Weight Of Poly(vinyl Stearate)supporting
confidence: 96%
See 1 more Smart Citation
“…Table V oligomer than a high molecular weight polymer. These results are consistent with characterization studies conducted by other researchers (32,45).…”
Section: Viscosity Average Molecular Weight Of Poly(vinyl Stearate)supporting
confidence: 96%
“…The values of the Mark-Houwink coefficients depend upon the nature of the polymer, the nature of the solvent, and the temperature. Based on the results of Burlant and Adicoff, the relationship between intrinsic viscosity and molecular weight was observed to be linear between 1,250 and 5,300 Da using these coefficients for poly(vinyl stearate) in benzene (32).…”
Section: Characterization Of Poly(vinyl Stearate)mentioning
confidence: 99%
“…Related measurements have also been made by Okamura, Hayashi and Nishii (1962 a) under different conditions of polymerization. Hayashi, Nishii and Okamura (1964 a) observed that, with radiation, the polymer crystals are twinned and a full analysis has been carried out by Carazzola et al (1963). Twinning is also reported in the identical polymer formed from tetroxane at 60"c but not at lOO"c, so that this is not an essential consequence of the crystal geometry, unless this is significantly affected by temperature.…”
Section: Oriented Polymer Crystalsmentioning
confidence: 99%
“…Trioxane has a hexagonal lattice, with a = 9.26 A and c = 8.60 A, and most reports (Sauter 1932, 1933, Moerman 1937, Okamura, Higashimura and Takeda 1962, Jamison and Noether 1963 give for polyoxymethylene a hexagonal unit cell with a = 4.46 A, c = 17-3 A ; the polymer forms a helix, with 9 monomer units per 5 turns. Carazzola et al (1963) summarize other polyoxymethylene modifications : a stretched fibre with a = 4.470 A, c = 56.00 A and 29 monomers per 16 turns, and an orthorhombic variant with a = 4.76 A, b = 7.66 A, c = 3.563 A and two monomers per unit cell.…”
Section: Oriented Polymer Crystalsmentioning
confidence: 99%
See 1 more Smart Citation